2020
DOI: 10.1002/chem.202001608
|View full text |Cite
|
Sign up to set email alerts
|

Design of Drug‐Like Protein–Protein Interaction Stabilizers Guided By Chelation‐Controlled Bioactive Conformation Stabilization

Abstract: Protein-protein interactions( PPIs) of 14-3-3 proteins are am odel system for studyingPPI stabilization. The complex natural product Fusicoccin As tabilizes many 14-3-3 PPIs but is not amenable for use in SAR studies, motivating the search for more drug-like chemical matter.H owever, drug-like 14-3-3PPI stabilizers enablingsuch studies have remainede lusive. An X-ray crystal structure of aP PI in complex with an extremelyl ow potencys tabilizer uncovered an unexpected non-protein interacting, ligand-chelated M… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 48 publications
1
32
0
Order By: Relevance
“…This series of pyrrolinones and pyrazoles were previously reported as stabilizers of the protein–protein interaction (PPI) involving the plant 14-3-3 proteins, 33 , 36 , 37 which are small adapter proteins that interact with functionally diverse protein partners to play important regulatory roles in vital cellular events including signal transduction, cell cycle control, and apoptosis. 38 An analysis combining the reported PPI stabilizing activity between 14-3-3 and the plant plasma membrane H + -ATPase 2 (PMA2) and PRI inhibitory activity against LIN28– let-7 revealed in this study showed intriguing SAR information surrounding the pyrrolinones and pyrazoles ( Figure S7 ).…”
mentioning
confidence: 99%
“…This series of pyrrolinones and pyrazoles were previously reported as stabilizers of the protein–protein interaction (PPI) involving the plant 14-3-3 proteins, 33 , 36 , 37 which are small adapter proteins that interact with functionally diverse protein partners to play important regulatory roles in vital cellular events including signal transduction, cell cycle control, and apoptosis. 38 An analysis combining the reported PPI stabilizing activity between 14-3-3 and the plant plasma membrane H + -ATPase 2 (PMA2) and PRI inhibitory activity against LIN28– let-7 revealed in this study showed intriguing SAR information surrounding the pyrrolinones and pyrazoles ( Figure S7 ).…”
mentioning
confidence: 99%
“…To test this methodology further, two additional putative stabilisers were introduced: fusicoccin J (FC-J), a biosynthetic precursor to FC-A; 25 and pyrrolidone 1 (Pyr1), a weak stabiliser of several 14-3-3-partner interactions. 26,29,30 On their own, like with FC-A, FC-J binds more strongly to 14-3-3s-ERa complexes albeit to a lesser extent with only moderate stabilisation (S P ¼ 0.96, Fig. S13 †).…”
Section: Screening For Stabilisers In a Drug Cocktailmentioning
confidence: 97%
“…In recent studies, the reverse experiment, monitoring 15 N, 2 H-labeled 14-3-3ΔC protein in 1 H, 15 N-TROSY-HSQC experiments [ 103 ], was used to investigate the stabilizing effect of several compounds on the interaction of 14-3-3 with different unlabeled peptide epitopes derived from 14-3-3 cargo proteins [ 104 106 ]. E.g., a semi-synthetic ligand consisting of a fusicoccane diterpene core combined with different sugar moieties was designed to improve its properties as molecular glue for the 14-3-3/p53 complex [ 105 ].…”
Section: Reviewmentioning
confidence: 99%